ECMO support for endoscopic resection of postpneumonectomy critical central airway obstruction - Alfonso Fiorelli; Marisa De Feo; Michele Torella; Fausto Ferraro; Andrea Bianco; Giuseppe Vicario; Francesca Capasso; Gaetana Messina; Giovanni Natale (Thoracic Cancer)
Abstract A 73‐year‐old woman was admitted to our hospital with severe respiratory distress due to postpneumonectomy neoplastic central airway obstruction. An emergency recanalization with rigid bronchoscopy (RB) was planned. Controlled and jet ventilation are routinely used to assure ventilation during RB, but the risk of inadequate oxygenation and removal of carbon dioxide was prohibitively high in this case due to the presence of a single lung. The use of venovenous extracorporeal membrane oxygenation was decided by multidisciplinary team to support ventilation during RB. Complete airway recanalization was successfully achieved without any complications. The patient was discharged 2 days later. Pathology revealed metastatic adenocarcinoma, and the patient was reviewed for oncologic treatment.